CSALP South Asia Quarterly Newsletter Vol.19 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Nepal state government officials present their future plans to invest in large scale Climate-Smart Village programmes at a workshop held in New Delhi